Phylogeography of the human mitochondrial haplogroup L3e: a snapshot of African prehistory and Atlantic slave trade - Bandelt, H.-J. (2020)
The mtDNA haplogroup L3e, which is identified by the restriction site 2349 MboI within the Afro-Eurasian superhaplogroup L3 (®3592 HpaI), is omnipresent in Africa but virtually absent in Eurasia (except for neighbouring areas with limited genetic exchange). L3e was hitherto poorly characterised in terms of HVS-I motifs, as the ancestral HVS-I type of L3e cannot be distinguished from the putative HVS-I ancestor of the entire L3 (differing from the CRS by a transition at np 16223). An MboI screening at np 2349 of a large number of Brazilian and Caribbean mtDNAs (encompassing numerous mtDNAs of African ancestry), now reveals that L3e is subdivided into four principal clades, each characterised by a single mutation in HVS-I, with additional support coming from HVS-II and partial RFLP analysis. The apparently oldest of these clades (transition at np 16327) occurs mainly in central Africa and was probably carried to southern Africa with the Bantu expansion(s). The most frequent clade (transition at np 16320) testifies to a pronounced expansion event in the mid-Holocene and seems to be prominent in many Bantu groups from all of Africa. In contrast, one clade (transition at np 16264) is essentially restricted to Atlantic western Africa (including Cabo Verde). We propose a tentative L3e phylogeny that is based on 197 HVS-I sequences. We conclude that haplogroup L3e originated in central or eastern Africa about 46,000 (³14,000) years ago, and was a hitchhiker of much later dispersal and local expansion events, with the rise of food production and iron smelting. Enforced migration of African slaves to the Americas translocated L3e mitochondria, the descendants of which in Brazil and the Caribbean still reflect their different regional African ancestries.